Friction in modern total hip arthroplasty bearings: Effect of material, design, and test methodology. (January 2016) - Scholl, Laura; Longaray, Jason; Raja, Lokesh; Lee, Reginald; Faizan, Ahmad; Herrera, Lizeth; Thakore, Mayur; Nevelos, Jim
The purpose of this study was to characterize the effect of a group of variables on frictional torque generated by acetabular components as well as to understand the influence of test model. Three separate test models, which had been previously used in the literature, were used to understand the effect of polyethylene material, bearing design, head size, and material combinations. Each test model differed by the way it simulated rotation of the head, the type of frictional torque value it reported (static vs. dynamic), and the type of motion simulated (oscillating motion vs. continuous motion). It was determined that not only test model may impact product ranking of fictional torque generated but also static frictional torque may be significantly larger than a dynamic frictional torque. In addition to test model differences, it was discovered that the frictional torque values for conventional and highly cross-linked polyethylenes were not statistically significantly different in the more physiologically relevant test models. With respect to bearing design, the frictional torque values for mobile bearing designs were similar to the 28-mm diameter inner bearing rather than the large diameter outer liner. Testing with a more physiologically relevant rotation showed that frictional torque increased with bearing diameter for the metal on polyethylene and ceramic on polyethylene bearings but remained constant for ceramic on ceramic bearings. Finally, ceramic on ceramic bearings produced smaller frictional torque values when compared to metal on polyethylene and ceramic on polyethylene groups.